Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Sure, let's simplify the expression [tex]\(\sqrt[4]{768 x^8 y^5}\)[/tex] step-by-step.
Given expression:
[tex]\[ \sqrt[4]{768 x^8 y^5} \][/tex]
Step 1: Factorize the number inside the radical:
[tex]\[ 768 = 256 \times 3 = (4^4) \times 3 \][/tex]
Therefore, we can write:
[tex]\[ 768 x^8 y^5 = (4^4 \cdot 3) x^8 y^5 \][/tex]
Step 2: Break the expression under the fourth root into separate fourth roots:
[tex]\[ \sqrt[4]{768 x^8 y^5} = \sqrt[4]{4^4 \cdot 3 x^8 y^5} \][/tex]
Step 3: Apply the fourth root to each factor separately:
[tex]\[ \sqrt[4]{4^4 \cdot 3 x^8 y^5} = \sqrt[4]{4^4} \cdot \sqrt[4]{3} \cdot \sqrt[4]{x^8} \cdot \sqrt[4]{y^5} \][/tex]
Step 4: Simplify each fourth root:
[tex]\[ \sqrt[4]{4^4} = 4 \quad \text{(since } (4^4)^{(1/4)} = 4\text{)} \][/tex]
[tex]\[ \sqrt[4]{x^8} = x^2 \quad \text{(since } (x^8)^{(1/4)} = x^2\text{)} \][/tex]
[tex]\[ \sqrt[4]{y^5} = y \cdot y^{1/4} \quad \text{(since } y^5 = y \cdot y^4\text{)} \][/tex]
Now, combining these simplified parts, we get:
[tex]\[ 4 \cdot 3^{1/4} \cdot x^2 \cdot y \cdot y^{1/4} \][/tex]
This can be written as:
[tex]\[ 4 \cdot 3^{1/4} \cdot x^2 \cdot y^{1+1/4} \][/tex]
[tex]\[ = 4 \cdot 3^{1/4} \cdot x^2 \cdot y \cdot y^{1/4} \][/tex]
Thus, the simplified expression is:
[tex]\[ 4 x^2 y \sqrt[4]{3 y} \][/tex]
Therefore, the correct answer is:
[tex]\[ \boxed{4 x^2 y \sqrt[4]{3 y}} \][/tex]
Given expression:
[tex]\[ \sqrt[4]{768 x^8 y^5} \][/tex]
Step 1: Factorize the number inside the radical:
[tex]\[ 768 = 256 \times 3 = (4^4) \times 3 \][/tex]
Therefore, we can write:
[tex]\[ 768 x^8 y^5 = (4^4 \cdot 3) x^8 y^5 \][/tex]
Step 2: Break the expression under the fourth root into separate fourth roots:
[tex]\[ \sqrt[4]{768 x^8 y^5} = \sqrt[4]{4^4 \cdot 3 x^8 y^5} \][/tex]
Step 3: Apply the fourth root to each factor separately:
[tex]\[ \sqrt[4]{4^4 \cdot 3 x^8 y^5} = \sqrt[4]{4^4} \cdot \sqrt[4]{3} \cdot \sqrt[4]{x^8} \cdot \sqrt[4]{y^5} \][/tex]
Step 4: Simplify each fourth root:
[tex]\[ \sqrt[4]{4^4} = 4 \quad \text{(since } (4^4)^{(1/4)} = 4\text{)} \][/tex]
[tex]\[ \sqrt[4]{x^8} = x^2 \quad \text{(since } (x^8)^{(1/4)} = x^2\text{)} \][/tex]
[tex]\[ \sqrt[4]{y^5} = y \cdot y^{1/4} \quad \text{(since } y^5 = y \cdot y^4\text{)} \][/tex]
Now, combining these simplified parts, we get:
[tex]\[ 4 \cdot 3^{1/4} \cdot x^2 \cdot y \cdot y^{1/4} \][/tex]
This can be written as:
[tex]\[ 4 \cdot 3^{1/4} \cdot x^2 \cdot y^{1+1/4} \][/tex]
[tex]\[ = 4 \cdot 3^{1/4} \cdot x^2 \cdot y \cdot y^{1/4} \][/tex]
Thus, the simplified expression is:
[tex]\[ 4 x^2 y \sqrt[4]{3 y} \][/tex]
Therefore, the correct answer is:
[tex]\[ \boxed{4 x^2 y \sqrt[4]{3 y}} \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.